Betacyanins enhance vitexin-2-O-xyloside mediated inhibition of proliferation of T24 bladder cancer cells. Issue 12 (4th November 2016) - Scarpa, E. S.; Emanuelli, M.; Frati, A.; Pozzi, V.; Antonini, E.; Diamantini, G.; Di Ruscio, G.; Sartini, D.; Armeni, T.; Palma, F.; Ninfali, P.
Abstract : An innovative betacyanin purification method and treatment of T24 urinary bladder cancer cells in combination with vitexin-2-O-xyloside. Abstract : Betacyanins (BC) were purified from beetroot ( Beta vulgaris var. rubra L.) and tested, alone or in combination with vitexin-2-O-xyloside (XVX) from Beta vulgaris var. cicla L., for their ability to reduce the proliferation rate in T24 bladder cancer cells. Combination of BC and XVX exhibited a synergistic effect concerning the inhibition of proliferation in T24 cancer cells at 24 and 48 h but not after 72 h of incubation. The induction of apoptosis was evidenced by means of fluorescence activated cell sorting (FACS) analysis, as well as through the increase in caspase 3 and 8 activities. Using RTqPCR experiments, it was shown that the combination of XVX + BC was able to enhance the expression levels of pro-apoptotic BAX and downregulate anti-apoptotic BIRC5 (survivin), as well as pro-survival CTNNB1 (β-catenin). The most evident effect of BC was the increase of the activity of caspase 8, leading to induction of extrinsic apoptosis. Moreover, XVX, BC and their combination showed no cytotoxic effect on normal human skin NCTC 2544 keratinocytes. These results demonstrated the efficacy and the mechanisms of the action of BC and XVX, extracted from edible plants, and suggested that a diet or a nutrition supplement, enriched with these bioactive molecules, could be used in the prevention of human bladder cancer.